Analysis of the Effect of Tax Compliance, Tax Avoidance, and Financial Reporting Quality on Company Financial Performance: A Case Study on a Manufacturing Company in Indonesia - Sri Adella Fitri; Eko Sudarmanto; Nabila Azura Qothrunnada; Pitri Wahyuni (Westscience Press, 2023)
This research investigates the intricate relationships among tax compliance, tax avoidance, financial reporting quality, and corporate financial performance in Indonesian manufacturing companies. Employing a quantitative approach, data were collected from 150 companies and analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS). The study found robust positive associations between tax compliance and financial reporting quality with corporate financial performance. Furthermore, a nuanced relationship emerged between tax avoidance and financial performance, highlighting the importance of moderation. The empirical findings offer valuable insights for practitioners, policymakers, and academics seeking to understand the dynamics of tax-related activities and financial outcomes in the Indonesian manufacturing sector.